Vaping in the Context of Delinquency Among Adolescents: A Cross-Sectional Comparison Among Alcohol and Cigarette Use - Maynard, Christian P. (Journal of drug issues, 2021)
Vaping has been increasing with Monitoring the Future, indicating nicotine vaping (2017–2018) having the largest single-year jump among any substance recorded in its 45-year history. Overall, research on vaping has been substantially limited, primarily in the context of vaping and delinquency. This study’s purpose is to examine how nicotine vaping compares with other common substances used by adolescents like alcohol and cigarettes within the context of delinquency. Using secondary data from Monitoring the Future: A Continuing Study of the Lifestyles and Values of Youth conducted in 2017, with a sample size of 8,467 participants, we find that ever-nicotine “vapers” were associated with less delinquency than ever-cigarette-using youth; however, these “vapers” were associated with more delinquency than ever-alcohol users. We interpret these results in the context of social bonding and social learning theory and policies to create awareness on the potential social implications of vaping.